Modeling the demand for cocaine - Everingham, Susan S.; Rydell, C. Peter; Rand eBooks (Santa Monica, CA : RAND, 1994)
This report documents the development of a two-state Markovian model of the demand for cocaine and includes the estimation of incidence, prevalence, cohort retention, and consumption. The Markovian model is required to fit (1) the overall prevalence data; (2) the fraction of all users who are heavy users in 1985, 1988, and 1990; and (3) the fraction of a cohort of initiates that is still using drugs ten years later, the ten-year cohort retention rate. The study states that the incidence of new users into light cocaine use has varied greatly over the years and is an input to the model; however, the model cannot predict future prevalence--it can only project prevalence given a hypothetical incidence scenario. The model also demonstrates that the fraction of all cocaine users who are heavy users has varied greatly over time, and that peak heavy usage followed peak incidence by about ten years. Consequently, the effect on heavy usage of government programs that reduce incidence (such as prevention programs) will only be realized many years later.
"Drug Policy Research Center."
Includes bibliographical references (p. 59-60).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Cocaine habit -- United States -- Mathematical models; Cocaine habit -- United States -- Prevention -- Mathematical models; Cocaine industry -- United States; Electronic books